(untitled) (Mediscope, 2022)
Background: Pneumonia is a recognized leading killer disease in under 5 children not only in Bangladesh but also in all developing countries. The presence of lower chest indrawing means that the child has severe pneumonia. This study aimed to determine the sensitivity, specificity and predictive values of chest indrawing in the diagnosis of severe pneumonia. Methods: This analytical study was conducted in the department of pediatrics, Sher-e-Bangla Medical College Hospital, Barisal, from January 2015 to December 2015. A total of 100 cases of severe pneumonia aged from 2 months to 5 years and similar numbers of suitably matched controls who fulfilled inclusion criteria were enrolled in this study. A detailed history was taken, a thorough physical examination was done, data were recorded in a preformed questionnaire and were analyzed using a scientific calculator. Results: Out of 100 cases, 80 (80%) and 100 controls, 72 (72%) were in the age group of 2 months to 1 year. Fast breathing was present in 98 (98%) cases and 88 (88%) controls. Chest indrawing was present in 56 (56%) cases and 42 (42%) controls. Roentgenographically, 44 (44%) cases revealed labor/segmental consolidation, and bilateral patchy consolidation was present in 56 (56%) cases. Among the control group, 28 (28%) patients had hyperlucency of peripheral lung fields in their chest X-rays. In this study, it was found that sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of chest indrawing in the diagnosis of severe pneumonia was 56%, 58%, 57.1% and 56.8% respectively. Conclusion: Chest indrawing alone is not a highly sensitive tool to predict severe pneumonia but in rural areas where X-ray facilities are not available, chest indrawing may play an important role in identifying children with possible severe pneumonia. Mediscope 2022;9(2): 54-59